On the solvability of a finite group with $S$-seminormal Schmidt subgroups - Zubei, E. V.; Knyagina, V. N.; Monakhov, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
A finite nonnilpotent group is called a Schmidt group if all its proper subgroups are nilpotent. A subgroup $A$ is called $S$-seminormal (or $SS$-permutable) in a finite group $G$ if there is a subgroup B such that $G = AB$ and $A$ is permutable with every Sylow subgroup of B. We establish the criteria of solvability and $π$ -solvability of finite groups in which someSchmidt subgroups are $S$-seminormal. In particular, we prove the solvability of a finite group in which all supersolubleSchmidt subgroups of even order are $S$-seminormal.